2000
DOI: 10.1136/heart.83.3.353
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal atrial and ventricular repolarisation resembling myocardial injury after tricyclic antidepressant drug intoxication

Abstract: A 44 year old woman was admitted to our intensive care unit five hours after ingestion of amitriptyline. She was comatose (Glasgow coma score 3) with dilated pupils non-reactive to light and accommodation. Biochemical findings and serum electrolytes were normal. Arterial blood gas measurements revealed a slight metabolic acidosis. She was immediately intubated and mechanically ventilated. Gastric lavage was performed for gastrointestinal V3 (large arrows). These become more prominent over time and persist for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…The predicted mean QTcB in the study mimicking that described by Zakynthinos et al [ 43 ] was 531 ms (520 ms observed in the clinic). In one out of ten simulated patients, arrhythmia was observed.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…The predicted mean QTcB in the study mimicking that described by Zakynthinos et al [ 43 ] was 531 ms (520 ms observed in the clinic). In one out of ten simulated patients, arrhythmia was observed.…”
Section: Resultssupporting
confidence: 79%
“…Because of lack of clinically observed precise data on time-matched concentrations of AT and NT, presentation of other PK metrics on the goodness of model prediction was not possible. The results of the cases are described in the order defined in the Materials and Methods section: The predicted mean QTcB in the study mimicking that described by Zakynthinos et al [ 43 ] was 531 ms (520 ms observed in the clinic). In one out of ten simulated patients, arrhythmia was observed.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Guthrie & Lott (1986) reported elevation of serum creatine kinase and MB fraction following an amitriptyline overdose without ECG changes in a patient who subsequently had normal coronary angiogram. Zakynthinos et al (2000) reported ECG changes mimicking acute myocardial infarction associated with tricyclic antidepressant overdose. ST segment elevation was reported in leads of DI, aVL, V1 and V2 mimicking a current of anteroseptal subepicardial injury after amitriptyline overdose, which persisted for four days.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid deterioration in mental status should be anticipated, as should abrupt onset of seizure activity [94,[100][101][102]. A prospective study of acute first-generation cyclic antidepressant ingestions showed the utility of the ECG in predicting cardiac dysrhythmias and seizures [103].…”
Section: Managementmentioning
confidence: 99%